Building Tolerance Character through Interfaith Experiential Learning: The Peace Tour Program at Pesantren-Based School Yogyakarta - Salsabila I'tilaful Adzibah; Dwi Ratnasari; Taufan Jannata; Lita Ariyanti; Muh Wasith Achadi (Southeast Asian Journal of Islamic Education, 2025)
This study explores the role of interfaith experiential learning in fostering tolerant character among students at SMA and Pesantren Bumi Cendekia Yogyakarta through the Peace Tour program. This qualitative research employs a phenomenological approach to uncover the lived experiences and religious reflections of students and teachers engaged in the Peace Tour program. The study involved three participants: one teacher and two students who directly participated in the activities. Data were collected through in-depth interviews and documentation, and analyzed using Miles and Huberman’s interactive model. The findings show that Peace Tour serves as a transformative educational practice that integrates cognitive, affective, and spiritual dimensions through direct interaction with religious others. Students experienced a shift from initial discomfort to deeper understanding and appreciation of diversity, fostering inclusive attitudes and reinterpretations of Islamic values in the context of pluralism. The program’s integration into the school’s co-curricular activities and reflective discussions within the pesantren further reinforced Islamic values of rahmatan lil ”˜alamin. This study concludes that interfaith experiential learning can serve as a pedagogical tool to instill tolerance and moderate character, as well as offer a best-practice model for Islamic educational institutions in multicultural societies. These findings imply that the Peace Tour program can be replicated and adapted by educational institutions and policymakers as an experiential learning strategy to foster tolerance and strengthen religious moderation among students.